Free Form Technology from Delft (2016)
The success of the Guggenheim Museum in Bilbao, designed and engineered by Frank O. Gehry and inaugurated in 1997, opened the eyes of the world to the plastic possibilities of Free Form Design. That is, on the side of architects and their admiring clients. Some architects draw up complicated but surprising and attractive Free Form Designs and win design competitions. The next step is to involve the manufacturing industry and the contractors in realizing these dreams. According to the author(s), the desire and logic for an adapted Free Form Technology will become became apparent after more designs. At Mick Eekhout’s design & build company Octatube the first experiences with Free Form Designs either failed, were aborted, were a disaster or led to unfortunate events such as the bankruptcy of competing firms who took on the projects without major Free Form Design experience. But Free Form design has matured nowadays. Many lessons can be learned from these early experiments, which is the main reason to share these experiences with readers of this book.